Weathering an unexpected financial shock: The role of cash grants on household finance and business survival - Justin Gallagher; Daniel Hartley; Shawn Rohlin (Federal Reserve Bank of Chicago, 2019)
We estimate the causal effect of cash grants on household finance and business survival following a natural disaster. Disaster-affected individuals in high damage blocks with access to cash grants have 17% less credit card debt following the disaster than those without access to cash grants. Grants do not reduce negative financial outcomes, but do decrease migration. The grants play a role in mitigating the effects of the shock to businesses; resulting in 18% more establishments and 29% more employees post-disaster in disaster-affected neighborhoods where resi- dents receive grants, relative to disaster-affected neighborhoods where they do not receive grants. These effects are concentrated among small non-manufacturing establishments that rely on local demand.
Keywords: D14; Q54; R11; 330; Katastrophe; Öffentliche Sozialleistungen; Wirkungsanalyse; USA